2012
DOI: 10.1118/1.4704644
|View full text |Cite
|
Sign up to set email alerts
|

A real‐time respiratory motion monitoring system using KINECT: Proof of concept

Abstract: It is feasible to use the KINECT for respiratory motion tracking. Traces are similar to those of a clinically used strain gauge system. The KINECT-based system provides a new and economical way to monitor respiratory motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 3 publications
0
65
1
1
Order By: Relevance
“…Kinect sensors can identify the motion of phantoms and volunteers, particularly periodic respiratory motion 8 , 11 . Our future work includes a patient study where the Kinect v2 system will be assessed as an alternative to visual monitoring for a voluntary breathing hold method for breast cancer patients (21) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kinect sensors can identify the motion of phantoms and volunteers, particularly periodic respiratory motion 8 , 11 . Our future work includes a patient study where the Kinect v2 system will be assessed as an alternative to visual monitoring for a voluntary breathing hold method for breast cancer patients (21) .…”
Section: Discussionmentioning
confidence: 99%
“…Whilst these provide no information about the internal anatomy of the patient, they may be used in conjunction with ionizing radiation imaging to provide frequent or continuous monitoring throughout the radiation delivery, as they do not contribute to the radiation dose burden. Recently some groups have investigated surface monitoring for radiotherapy and PET imaging using consumer‐grade sensors designed for the entertainment industry — the Microsoft Kinect devices 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 . The potential advantage of commercial off‐the‐shelf (COTS) devices is the low cost (less than ~$1,400 for a Kinect device and accessories compared to upwards of $250,000 for the commercial medical systems), thus enabling many sensors in many rooms, depending on the application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research into respiratory motion tracking using the Kinect utilized either the Kinect v1 or required a translational marker to be placed on the patient's surface or embedded within clothing worn by the patient,9, 10, 11 similar to other respiratory tracking systems currently available for purchase. The latest version of the Kinect contains higher resolution sensors than the previous model, which helps remove the requirement for a translational marker to track respiratory motion.…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al showed that a respiratory curve was measured from depth image taken by Kinect v1 [16]. They evaluated the cross correlation coefficients between detected respiratory curves by a Kinect and a strain gauge system.…”
Section: Introductionmentioning
confidence: 99%